A Theory of Education and Health - Titus J. Galama; Hans van Kippersluis (Tinbergen Institute, 2015)
This paper presents a unified theory of human capital with both health capital and, what we term, skill capital endogenously determined within the model. By considering joint investment in health capital and in skill capital, the model highlights similarities and differences in these two important components of human capital. Health is distinct from skill: health is important to longevity, provides direct utility, provides time that can be devoted to work or other uses, is valued later in life, and eventually declines, no matter how much one invests in it (a dismal fact of life). Lifetime earnings are strongly multiplicative in skill and health, so that investment in skill capital raises the return to investment in health capital, and vice versa. The theory provides a conceptual framework for empirical and theoretical studies aimed at understanding the complex relati onship between education and health, and generates several new testable predictions.
Keywords: D91; I10; I12; J00; J24; 330; health investment; lifecycle model; human capital; health capital